The electronic structure of lithium metagallate - Johnson, N W; McLeod, J A; Moewes, A (Journal of physics. Condensed matter, 2011)
Herein we present a study of the electronic structure of lithium metagallate (LiGaO(2)), a material of interest in the field of optoelectronics. We use soft x-ray spectroscopy to probe the electronic structure of both the valence and conduction bands and compare our measurements to ab initio density functional theory calculations. We use several different exchange-correlation functionals, but find that no single theoretical approach used herein accurately quantifies both the band gap and the Ga 3d(10) states in LiGaO(2). We derive a band gap of 5.6 eV, and characterize electron hybridization in both the valence and conduction bands. Our study of the x-ray spectra may prove useful in analysing spectra from more complicated LiGaO(2) heterostructures.